Development of Cells for Generation of Potential Difference from Aloe Vera - Gandole, Yogendra B.; Wajire, Gajanan S. (Journal of Science and Technology, 2016)
Today’s need of this modern world is to introduce the renewable, sustainable, pollution free and an efficient energy sources. In this paper, some fundamental investigations are demonstrated for generating an electrical energy from living plants like Aloe Vera. The energy is generated by embedding the electrodes and cells into the plant to allow flow of ions using redox reaction. Here multiple tests have been conducted using different type of electrodes, cells and plants as an attempt to determine the characteristics of the generating system. Though the research work in this field is in infancy, we were able to produce the potential difference of about 1.221V using single pair of electrode and cell. Such hypothesis has been tested at different time of the day and different seasons of the year. Also, lots of new types of materials has been tested and used in combination to give better performance for the development of such a green energy. In future, this green energy could be used for low power electrical and electronic appliances for their operation